Accuracy of electoral registers and Family Practitioner Committee lists for population studies of the very elderly. Issue 4 (December 1989) - Bowling, A; Hart, D; Silman, A
Abstract : STUDY OBJECTIVE: The purpose of the study was to assess the accuracy of Family Practitioner Committee (FPC) lists for identifying very elderly people registered with general practitioners. DESIGN: The accuracy of available FPC lists was checked against the most recent electoral register to determine which recorded individuals were still living at their FPC registered addresses. This was followed by a postal and home visit enquiry to validate the accuracy of the electoral register. SETTING: The study was carried out in the London borough of Hackney. PARTICIPANTS: The investigation was confined to persons aged 85 and over. RESULTS: Of a total of 3018 people listed as being 85 years or over by the FPC, 1183 (39%) were listed on the electoral register. Of these, 751 (63%) were living at their registered address, ie 25% of the people in the original FPC list. A further 154 (5%) of the original list were not recorded on the electoral register but were alive at the FPC recorded address. CONCLUSIONS: the use of FPC lists alone to identify the very elderly in an inner city population is too inaccurate to be of value. The combined use of FPC lists and the electoral register is better but one in six persons will still be missed.